ANALYSIS OF DESIGN AESTHETICS (DA) ON THE USE OF KAI ACCESS WITH MULTI MOTIVE INFORMATION SYSTEM CONTINUANCE (MISC) THEORY: ANALISIS DESIGN AESTHETICS (DA) TERHADAP PENGGUNAAN KAI ACCESS DENGAN TEORI MULTI MOTIVE INFORMATION SYSTEM CONTINUANCE (MISC) - andini, arifah mutia; Bisma, Rahadian (Journal of Emerging Information Systems and Business Intelligence, 2023)
Abstract-This study analyzes the influence of user motivation in continuing to use the KAI Access train ticket booking application using the Multi Motive Information System Continuance (MISC) theory. This study aims to analyze the design aesthetics of the KAI Access application. This research is important for PT Kereta Api Indonesia to maintain customer retention and improve the quality of their services. This study found that the design aesthetics of the KAI Access application had no effect, but appropriate design expectations, ease of use, hedonic expectations, intrinsic expectations, extrinsic expectations, hedonic disconfirmation, intrinsic disconfirmation, extrinsic disconfirmation, attitudes, satisfaction, hedonic performance, intrinsic performance, and extrinsic performance significantly affects the intention to continue using KAI Access.